2005
DOI: 10.1128/ec.4.5.837-848.2005
|View full text |Cite
|
Sign up to set email alerts
|

The zrfA and zrfB Genes of Aspergillus fumigatus Encode the Zinc Transporter Proteins of a Zinc Uptake System Induced in an Acid, Zinc-Depleted Environment

Abstract: Zinc is an essential micronutrient that cells must obtain from the environment in order to develop their normal growth. Previous work performed at our laboratory showed that the synthesis of immunodominant antigens from Aspergillus spp., including A. fumigatus, was up-regulated by a low environmental concentration of zinc. These results suggested that a tightly regulated system for the fungus to grow under zinc-limiting conditions must underlie the ability of A. fumigatus to acquire zinc in such environments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
1
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 35 publications
3
96
1
10
Order By: Relevance
“…The majority of genes in the Δ gliP mutant were expressed at wild-type levels in vivo (Table S1). However, relative to the wild-type strain, the Δ gliP mutant had increased expression of zrfA , which specifies a zinc transporters, and of aspf2 , which is required for growth under zinc-limited conditions (Table 1) [30,31]. These genes were also significantly up-regulated when the nanoString data were normalized to the gpdA housekeeping gene.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of genes in the Δ gliP mutant were expressed at wild-type levels in vivo (Table S1). However, relative to the wild-type strain, the Δ gliP mutant had increased expression of zrfA , which specifies a zinc transporters, and of aspf2 , which is required for growth under zinc-limited conditions (Table 1) [30,31]. These genes were also significantly up-regulated when the nanoString data were normalized to the gpdA housekeeping gene.…”
Section: Resultsmentioning
confidence: 99%
“…All strains belonged to the Mycology Reference Laboratory collection, except the strain AF14 16 that was kindly donated by Dr. J.A. Calera.…”
Section: Methodsmentioning
confidence: 99%
“…We first showed that the ZrfA/ZrfB zinc uptake system of A. fumigatus, which somewhat resembles the Zrt1/Zrt2 zinc uptake system of S. cerevisiae, functions to obtain zinc mainly from acid, zinc-limiting environments (45). However, in contrast to S. cerevisiae, Aspergillus species exhibit strong metabolic versatility and show similar growth rates over a pH range between 3.0 and 10.5 (51).…”
mentioning
confidence: 99%